The Characteristics of the Thinking Scale of Class X Students on the Water Cycle Material - Devi Oktaviani Safitri; Azizul Ghofar Candra Wicaksono; Prasetiyo (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aims to describe the characteristics of the systems thinking abilities of Class X students in the water cycle material across the cognitive and affective domains. The research uses a quantitative descriptive approach with a survey method. The research  sample consis of 80 Class X students from SMA Negeri 10 Semarang, selected through purposive sampling. The research instruments included a multiple-choice test to measure systems thinking abilities in the cognitive domain and attitude questionnaires to measure the affective domain. The instruments were developed based on a hierarchical systems thinking framework and a systems thinking scale. The data were analyzed descriptively and tested using the Pearson Product Moment correlation. The results show that the cognitive domain systems thinking abilities are in the high category, particularly at the analysis level, where more than 70% of students reached the high category, while the synthesis and implementation levels are in the moderate category. The affective systems thinking abilities are generally in the moderate category, with percentages ranging from 52.50% to 81.25%. There is a very strong and significant relationship between the cognitive and affective domains at the same level is considered low to moderate.These findings highlight the need for more context-rich integrative learning to optimize students’ systems thinking abilities.